1987
DOI: 10.1111/j.1348-0421.1987.tb01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Defective Provirus of Bovine Leukemia Virus

Abstract: Defective proviruses of bovine leukemia virus (BLV) in the genomes of infected cells were investigated by using Southern blotting hybridization analysis with various portions of a cloned BLV DNA as probes. When nine independent tumors of enzootic bovine leukosis with a single proviral copy per cell were examined, a single defective provirus of BLV was found in one tumor and also in a bovine B cell line derived from this tumor. Hybridization analysis of this defective provirus revealed that it underwent deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The Tax orf is the largest of the X region located between the env gene and the 3' LTR (Figure 2). The Tax protein is a target of the host immune response with T and B epitopes corresponding to regions 110–130/131–150 and 261–280, respectively [182]. …”
Section: The Blv Genomementioning
confidence: 99%
“…The Tax orf is the largest of the X region located between the env gene and the 3' LTR (Figure 2). The Tax protein is a target of the host immune response with T and B epitopes corresponding to regions 110–130/131–150 and 261–280, respectively [182]. …”
Section: The Blv Genomementioning
confidence: 99%
“…However, it is unknown how the expression of BLV is restricted in vivo to levels that are undetectable by conventional methods. Several candidate mechanisms for silencing have been proposed: (i) accumulation and export of unspliced viral mRNA by Rex protein (10), (ii) inactivation of a viral protein(s) caused by mutation or deletion of the proviral genome (29,36,48,49), (iii) blockage of the transcription of the viral LTR by DNA methylation (11,41), (iv) absence and/or inactivation of cellular factors that can activate LTR-directed transcription (2,24,28,39), and (v) induction and/or activation of cellular factors that repress the viral transcription (39,60). Recently, Van Den Broeke et al (49) reported that the occurrence of a deficient Tax protein as a result of mutation may play an important role in the silenced phenotype observed in BLV-induced ovine B-cell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…relation probably exists between clinical subtypes and the defective viruses (40,41). Likewise, defective proviruses have been found in BLV-induced lymphoid tumors and cell lines which have been established from leukemic cells of BLV-infected hosts with lymphosarcomas (16,23,32). Deletions were found in 1 of 9 (11.1%) (32) and in 4 of 17 (23.5%) (23) cases of EBL, and they involved sequences located mainly in the 5Ј half of the provirus as well as those in HTLV-1.…”
mentioning
confidence: 98%